Reduced repair of 8-hydroxyguanine in the human breast cancer cell line, HCC1937 - Nyaga, Simon G (BioMed Central, 2006)
BACKGROUND: Breast cancer is the second leading cause of cancer deaths in women in the United States. Although the causes of this disease are incompletely understood, oxidative DNA damage is presumed to play a critical role in breast carcinogenesis. A common oxidatively induced DNA lesion is 8-hydroxyguanine (8-OH-Gua), which has been implicated in carcinogenesis. The aim of this study was to investigate the ability of HCC1937 and MCF-7 breast cancer cell lines to repair 8-OH-Gua relative to a nonmalignant human mammary epithelial cell line, AG11134. METHODS: We used oligonucleotide incision assay to analyze the ability of the two breast cancer cell lines to incise 8-OH-Gua relative to the control cell line. Liquid chromatography/mass spectrometry (LC/MS) was used to measure the levels of 8-OH-Gua as its nucleoside, 8-OH-dG in the cell lines after exposure to H(2)O(2 )followed by 30 min repair period. Protein expression levels were determined by Western blot analysis, while the hOGG1 mRNA levels were analyzed by RT-PCR. Complementation of hOGG1 activity in HCC1937 cells was assessed by addition of the purified protein in the incision assay, and in vivo by transfection of pFlagCMV-4-hOGG1. Clonogenic survival assay was used to determine sensitivity after H(2)O(2)-mediated oxidative stress. RESULTS: We show that the HCC1937 breast cancer cells have diminished ability to incise 8-OH-Gua and they accumulate higher levels of 8-OH-dG in the nuclear genome after H(2)O(2 )treatment despite a 30 min repair period when compared to the nonmalignant mammary cells. The defective incision of 8-OH-Gua was consistent with expression of undetectable amounts of hOGG1 in HCC1937 cells. The reduced incision activity was significantly stimulated by addition of purified hOGG1. Furthermore, transfection of pFlagCMV-4-hOGG1 in HCC1937 cells resulted in enhanced incision of 8-OH-Gua. HCC1937 cells are more sensitive to high levels of H(2)O(2 )and have up-regulated SOD1 and SOD2. CONCLUSION: This study provides evidence for inefficient repair of 8-OH-Gua in HCC1937 breast cancer cell line and directly implicates hOGG1 in this defect.